Bovid mortality patterns from Kanjera South, Homa Peninsula, Kenya and FLK-Zinj, Olduvai Gorge, Tanzania: Evidence for habitat mediated variability in Oldowan hominin hunting and scavenging behavior. Issue 131 (June 2019) - Oliver, James S.; Plummer, Thomas W.; Hertel, Fritz; Bishop, Laura C.
Abstract: The archaeological record has documented Oldowan hominin occupation of habitats ranging from open grasslands to riparian forest by 2.0 Ma. Despite this we have a poor understanding of whether hominin foraging behavior varied in different environmental settings. We compared bovid mortality profiles from the two largest Oldowan zooarchaeological samples, one from a grassland (Excavation 1, Kanjera South, Kenya) and another from a woodland (FLK Zinj, Olduvai Gorge, Tanzania) with bovid mortality samples created by African carnivores in different habitats. Kanjera hominins frequently had early access, likely through hunting, to small (size 1 ≤ 23 kg and size 2 = 24–112 kg) juvenile bovids, creating a mortality pattern similar to that created by grassland dwelling carnivores. Kanjera hominins had more mixed access to large (size 3 = 113–340 kg), often juvenile, bovids and frequently scavenged heads. In contrast, previous work has shown that the few small bovids at FLK-Zinj were predominantly older individuals. Prime adults dominated the FLK-Zinj large bovid sample, leading to a mortality pattern similar to that created by carnivores occupying more closed habitats. Variation in bovid body size and mortality profiles between these archaeological assemblages may reflect the challenges of acquiring fauna in open versus closed habitats with a simple hunting toolkit. The heterogeneous woodland habitat of FLK-Zinj would have provided more opportunities to ambush prey, whereas on grasslands with more limited concealment opportunities Kanjera hominins focused their efforts on vulnerable juvenile prey, some likely acquired after short chases.